2009
DOI: 10.1088/1742-5468/2009/07/p07046
|View full text |Cite
|
Sign up to set email alerts
|

Mapping stochastic processes onto complex networks

Abstract: We introduce a method by which stochastic processes are mapped onto complex networks. As examples, we construct the networks for such time series as those for free-jet and low-temperature helium turbulence, the German stock market index (the DAX), and the white noise. The networks are further studied by contrasting their geometrical properties, such as the mean-length, diameter, clustering, average number of connection per node. By comparing the network properties of the investigated original time series with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 29 publications
0
65
0
2
Order By: Relevance
“…. , S K } allows considering the transition probabilities π α,β = P (x i+1 ∈ S β | x i ∈ S α ) between these classes in terms of a weighted and directed network [Nicolis et al, 2005;Dellnitz et al, 2006;Gao & Li, 2005;Li & Gao, 2006;Gao et al, 2007;Li & Wang, 2006;Li & Wang, 2007;Shirazi et al, 2009;Padberg et al, 2009]. This approach is equivalent to applying a symbolic discretization with static grouping [Daw et al, 2003;Donner et al, 2008] to the phase space of the studied system.…”
Section: Transition Networkmentioning
confidence: 99%
“…. , S K } allows considering the transition probabilities π α,β = P (x i+1 ∈ S β | x i ∈ S α ) between these classes in terms of a weighted and directed network [Nicolis et al, 2005;Dellnitz et al, 2006;Gao & Li, 2005;Li & Gao, 2006;Gao et al, 2007;Li & Wang, 2006;Li & Wang, 2007;Shirazi et al, 2009;Padberg et al, 2009]. This approach is equivalent to applying a symbolic discretization with static grouping [Daw et al, 2003;Donner et al, 2008] to the phase space of the studied system.…”
Section: Transition Networkmentioning
confidence: 99%
“…The time series firstly is transformed into networks and then analyzed with various complex network tools [25][26][27][28]. Shirazi et al [29] demonstrated that the time series can be reconstructed with high precision by means of a simple random walk on their corresponding networks. The interaction of financial markets naturally constitutes a complex system in which the stock data are a multivariate time series (MTS) [30] of information in each part of the complex system.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a graphtheoretical approach in time series analysis has been developed, and the network-based theories have been applied in many disciplines such as biology, sociology, physics, climatology, and neurosciences [24][25][26][27][28][29][30][31] . In this approach, a time series is mapped into a (complex) graph, and the characteristics of the time series are believed to be inherited in the resulting network, which can be analyzed from a complex network perspective.…”
Section: Introductionmentioning
confidence: 99%